Perubahan Hematologi Ikan Mas Komet (Carassius auratus auratus) Akibat Infestasi Argulus japonicus Jantan Dan Argulus japonicus Betina [Hematologic Changes Comet Goldfish (Carassius auratus auratus) as a Result of Infestation Argulus japonicus Males And Argulus japonicus Females] - Kismiyati Kismiyati; Laksmi Sulmartiwi; Norma Isnawati (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Diseases of the ornamental fish farming is mainly caused by ectoparasites. Ectoparasites are one cause of the declining value of the commodity selling ornamental fish in Indonesia. Argulus japonicus acute infestation levels could cause death and economic loss to farmers.The aim of this study was to determine the hematologic changes comet goldfish (Carassius auratus auratus) were infested A. japonicus males and females at different degrees of infestation. Research conducted at the Laboratory of Fisheries and Marine Laboratory of Airlangga University and the University of Airlangga Veterinary clinic and Center for Health Laboratory Surabaya in October 2014. The method used in this study is the experimental method. Data hemoglobin, hematocrit, erythrocytes, leukocytes were analyzed using ANOVA to determine the effect of treatment in the study group. This study used four treatments and five replicates with two groups. The variables were observed in this study were hematologic changes due to infestations of A. japonicus. Scoring is done to determine the hematologic changes comet goldfish.